Cognitive linguistics - Croft, William; Cruse, D. A. (Cambridge, U.K. ; New York : Cambridge University Press, 2004)
Cognitive Linguistics argues that language is governed by general cognitive principles, rather than by a special-purpose language module. This introductory textbook surveys the field of cognitive linguistics, presenting its theoretical foundations and the arguments supporting it. Clearly organised and accessibly written, it provides a useful introduction to this fast-growing area.
Cover; Half-title; Title; Copyright; Contents; Figures; Tables; Preface; 1 Introduction: what is cognitive linguistics?; PART I A conceptual approach to linguistic analysis; PART II Cognitive approaches to lexical semantics; PART III Cognitive approaches to grammatical form; References; Author index; Subject index.
Includes bibliographical references (pages 330-343) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Cognitive grammar; Grammaire cognitive; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax; Cognitive grammar; Kognitive Semantik; Metapher; Polysemie; Kognitive Linguistik; Semantik; Cognitieve linguïstiek.; Lingüística cognitiva; Electronic book